2021
DOI: 10.1063/5.0067302
|View full text |Cite
|
Sign up to set email alerts
|

Conduction channel configuration controlled digital and analog response in TiO2-based inorganic memristive artificial synapses

Abstract: The operating current regime is found to play a key role in determining the synaptic characteristic of memristor devices. A conduction channel that is formed using high current compliance prior to the synaptic operation results in digital behavior; the high current stimulus forms a complete conductive filament connecting the cathode and anode, and the high electric field promotes abrupt redox reactions during potentiation and depression pulsing schemes. Conversely, the conduction can be reconfigured to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…To reduce the complexity of the memristor circuit and its operation, the development of a digital–analog integrated memristor is critical in developing neuromorphic computing systems. Recently, several works have reported efforts to realize a digital-to-analog transition in a memristive system. For instance, Kim et al reported the transition between digital and analog behavior in a NiO x -based memristor . However, rather than in situ control, this digital-to-analog transition was achieved by regulating the oxygen vacancy content of NiO during the preparation process, which cannot accomplish the coexistence of digital and analog states in a single device, thus limiting its practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the complexity of the memristor circuit and its operation, the development of a digital–analog integrated memristor is critical in developing neuromorphic computing systems. Recently, several works have reported efforts to realize a digital-to-analog transition in a memristive system. For instance, Kim et al reported the transition between digital and analog behavior in a NiO x -based memristor . However, rather than in situ control, this digital-to-analog transition was achieved by regulating the oxygen vacancy content of NiO during the preparation process, which cannot accomplish the coexistence of digital and analog states in a single device, thus limiting its practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Memristor and memristive circuit are one of the candidates for the advanced computing architecture which differs from the conventional von Neumann architecture suffering from data movement between the central processing unit and memory. The memristor has been widely developed for promising nonvolatile memory and artificial synapse device due to its simple two-terminal structure, fast switching speed, and low power consumption [ 1 , 2 , 3 , 4 , 5 ]. In addition, memristive circuit can implement a nonvolatile logic-in-memory circuit that enables normally off computing [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%